Catastrophic injuries in wrestlers - Boden, B. P.; Lin, W.; Young, M.; Müller, F. O. (The American Journal of Sports Medicine, 2002)
BACKGROUND: There is a paucity of comprehensive information on catastrophic wrestling injuries. OBJECTIVE: Our objective was to develop a profile of catastrophic injuries in wrestling and a list of relevant risk factors. STUDY DESIGN: Retrospective review. METHODS: We retrospectively reviewed 35 incidents that were reported to the National Center for Catastrophic Sports Injury Research over an 18-year period from 1981 until 1999. RESULTS: Except in the case of one male college athlete, all injuries occurred in male high school wrestlers. There were 2.11 direct catastrophic injuries per year or 1 per 100,000 participants. The majority of injuries occurred in match competitions (80%), with a trend toward more injuries in the low- and middle-weight classes. The position most frequently associated with injury was the defensive position during the takedown maneuver (74%), followed by the down position (23%), and the lying position (3%). Catastrophic injuries included 27 cervical fractures or major cervical ligament injuries, 4 spinal cord contusions with transient quadriparesis, 3 severe head injuries, and an acutely herniated lumbar disc. The injuries resulted in quadriplegia in 11, residual neurologic deficits in 6, paraplegia in 1, and death in 1 head-injured athlete. CONCLUSIONS: Although catastrophic injuries in wrestling are rare, they do occur. Referees can help prevent such injuries by strictly enforcing penalties for slams and by gaining more awareness of dangerous holds. Coaches may also prevent serious injuries by emphasizing proper wrestling techniques.